Implementasi Motode Qira’at Sab’ah dalam Al-Quran Surat Al-An’am Ayat 101-108 - Nina Arnita Pulungan; Novria Grahmayanuri; Muhammad Iqbal (Edudeena : Journal of Islamic Religious Education, 2022)
Abstrack: The Qur’an has certain way of reading (qirā'at) that differs from one another according to the school of thought. This way of reading arose because of the different dialects of various ethnic elements at the time of the Prophet. This study discusses the implementation of Qira'at Sab'ah in the al-Quran by the version of Imam Ibnu Katsir History of al-Bazzy and Qunbul. The puspose of this study is to explore on the implementation of the qira'at Sab'ah in the recitation of the letters contained on the al-Quran at Surah al-An’am verses 101-108, as well as describe the process of implementing the sab'ah reading mode in the al-Quran read by reciter'. This research presents a qualitative data analysis. The data of this research sources from a video recording of Reading with Qira’at Sab'ah Mode which is carried out by a reciter named Muhammad Azroi Hasibuan at MTQN XXVIII. In this research, the data are compiled by applying documentary techniques, particularly in content analysis. The results of this research indicate there is an implementation of the Qira’at Sab’ah mode in Surah al-An'am verses 101-108 with the application of Qira'at Imam Ibn Kathir, the history of al-Bazzy and Qunbul, started with the recitation of isti'adzah which is separated or interrupted with basmalah. In addition, reading Mad Shilah Mim Jama', reading Qashr Mad Munfashil, Mad Muttasil with at-Tawassuth Shilah Ha 'Kinayah at Washal. Abstrak: Al-Quran memiliki cara tertentu dalam membaca al-Quran (qirā‘at) dengan memiliki perbedaan satu dengan yang lainnya sesuai dengan mazhabnya. Cara baca ini muncul disebabkan oleh dialek yang berbeda dari bermacam unsur etnik di masa Rasulullah. Penelitian ini mengkaji tentang Implementasi Qira'at Sab'ah dalam Al-Quran versi Imam Ibnu Katsir riwayat Al-Bazzy dan Qunbul. Kajian ini bertujuan untuk mengelaborasi penerapan qira'at sab'ah dalam bacaan surat-surat pada al-Quran dalam Surah al-An'am ayat 101-108, serta mendeskripsikan proses pelaksanaan qira’at sab’ah oleh qari'. Kajian ini mengaplikasikan metode kualitatif. Data pada kajian ini bersumber dari rekaman video MTQ yang diunduh dari internet dengan Mode Bacaan Qira’at Sab’ah yang dilakukan oleh seorang qari bernama Muhammad Azroi Hasibuan di MTQN XXVIII. Temuan penelitian menunjukkan bahwa terdapat implementasi mode Qira’at Sab'ah dalam Surah Al-An'am ayat 101-108 dengan penerapan Qira'at Imam Ibnu Katsir, sejarah Al-Bazzy dan Qunbul, dimulai dengan bacaan isti'adzah yang dipisahkan atau disela dengan basmalah. Selain itu, membaca Mad Shilah Mim Jama', membaca Qashr Mad Munfashil, Mad Muttasil dengan at-Tawassuth Shilah Ha 'Kinayah saat Washal.